2010
DOI: 10.4049/jimmunol.1001037
|View full text |Cite
|
Sign up to set email alerts
|

The Crucial Role of GATA-1 in CCR3 Gene Transcription: Modulated Balance by Multiple GATA Elements in the CCR3 Regulatory Region

Abstract: GATA-1, a zinc finger-containing transcription factor, regulates not only the differentiation of eosinophils but also the expression of many eosinophil-specific genes. In the current study, we dissected CCR3 gene expression at the molecular level using several cell types that express varying levels of GATA-1 and CCR3. Chromatin immunoprecipitation analysis revealed that GATA-1 preferentially bound to sequences in both exon 1 and its proximal intron 1. A reporter plasmid assay showed that constructs harboring e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…However, we observed the GATA-1 occupancy regardless of cell types (data not shown). Lack of the differential binding seems to be due to the fact that the current ChIP assay cannot discern, if any, differential binding of GATA-1 to these GATA sites, probably because the fourth and fifth GATA elements are positioned at only about 100 base pair away from the first GATA element that shows a high affinity binding for GATA-1, as seen in previous results (Kim et al, 2010). …”
Section: Resultsmentioning
confidence: 49%
See 4 more Smart Citations
“…However, we observed the GATA-1 occupancy regardless of cell types (data not shown). Lack of the differential binding seems to be due to the fact that the current ChIP assay cannot discern, if any, differential binding of GATA-1 to these GATA sites, probably because the fourth and fifth GATA elements are positioned at only about 100 base pair away from the first GATA element that shows a high affinity binding for GATA-1, as seen in previous results (Kim et al, 2010). …”
Section: Resultsmentioning
confidence: 49%
“…The fourth and the fifth GATA sites in exon 1 are claimed to constitute a double-GATA site as a key element that dictates GATA-1-mediated transcription of many eosinophil-specific genes (Rothenberg and Hogan, 2006). However, our previous study using a reporter plasmid assay in K562 cells demonstrated that the first GATA site is solely responsible for GATA-1-mediated transactivation of CCR3 , while the fourth and fifth GATA sites play inhibitory roles in CCR3 transcription, with high affinity binding for GATA-1 comparable to that of the first GATA element (Kim et al, 2010). The differential contributions of these GATA sites to CCR3 transcription were almost exactly duplicated in A549 cells (Supplemental Data Figure S1), and GATA-1 bound to sequences in exon 1 of CCR3 genes, as analyzed by ChIP assay (Supplemental Data Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations